(untitled) (Письма в ЭЧАЯ, 2024)
Abstract__ This research study focused on the production and application of mixture (silver-gold) nanoparticles, which can be utilized in radiation protection and environmental cleaning applications. Because the production of free radicals causes tissue cancer and has harmful effects on biological tissues, it is important to protect against and reduce the risk of gamma radiation. In vitro results indicate the ability of the mixture (silver-gold) nanoparticles as an anti-oxidant agent in water samples. The investigation with an in vivo study demonstrates that a mixture of (silver-gold ) nanoparticles is effective in protecting some mice tissues (liver and kidney) from gamma radiation after whole-body exposure to a 1.2Sv equivalent dose. Histopathological analysis of the tissue cells showed that the dose injection of nanoparticles protected the tissue cells from radiation-induced damage. The current study will encourage and assist the development of novel and inventive radiation protection strategies that make use of nanotechnology.